2014
DOI: 10.1007/s11095-014-1447-7
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase Enzymosomes: Carrier Capacity Optimization, in Vivo Behaviour and Therapeutic Activity

Abstract: SOD-enzymosomes were shown to be a new and successful therapeutic approach to oxidative stress-associated inflammatory situations/diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…However, mitochondria also prevent ROS and regulate the steady-state concentration of O2 •− in the intermembrane space by three different mechanisms. The first mechanism involves the enzyme superoxide dismutase (SOD) ( 39 ), acting through the dismutation of O 2 and producing hydrogen peroxide (H2) in fully reduced water product. There are two types of SOD including the specific mitochondrial matrix containing the manganese active site ( 40 ) (MnSOD or SOD2), which eliminates O2 •− formed in the matrix or on the inner side of the inner membrane, and SOD containing copper and zinc ( 41 ) instead of manganese SOD (copper-zinc SOD or SOD1) located in the cytoplasm of eukaryotic cells.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, mitochondria also prevent ROS and regulate the steady-state concentration of O2 •− in the intermembrane space by three different mechanisms. The first mechanism involves the enzyme superoxide dismutase (SOD) ( 39 ), acting through the dismutation of O 2 and producing hydrogen peroxide (H2) in fully reduced water product. There are two types of SOD including the specific mitochondrial matrix containing the manganese active site ( 40 ) (MnSOD or SOD2), which eliminates O2 •− formed in the matrix or on the inner side of the inner membrane, and SOD containing copper and zinc ( 41 ) instead of manganese SOD (copper-zinc SOD or SOD1) located in the cytoplasm of eukaryotic cells.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…It was previously reported that the FITC, UCU and CAT molecules competitively interacted with the interfacial regions of zwitterionic enzymosomal membranes through electrostatic and hydrophobic interactions 9 34 . Corvo et al 35 recently reported that superoxide dismutase (SOD) could covalently attach to the outer surfaces of enzymosomes, and this type of enzymosomes showed earlier therapeutic activities than did both free SOD and another type of enzymosomes with SOD encapsulated in the aqueous interior. The UCU molecules existed in the ESU or ESUC in three ways: (1) The UCU or UCU in the presence of CAT was attached the outer surface of ESU or ESUC, which in clinical practice might, enable rapid enzyme efficacy for patients; (2) The UCU or UCU in the presence of CAT was attached the inner surface of ESU or ESUC; and (3) the UCU or UCU in the presence of CAT was just entrapped inside the ESU or ESUC without attaching to the inner surfaces of membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same liposome with antioxidant enzyme superoxide dismutase covalently linked to the distal end of DSPE-PEG showed an enhanced therapeutic result in the IRI. 18 This opens the possibility to access diagnostic and therapy with the same nanoplatform.…”
Section: Magnetoliposomesmentioning
confidence: 99%